Measurement of inkjet droplet speed using interference fringe by diffracted light - Dong Yeol Shin; Yoon Jae Moon; Byeong-Kwon Ju; Kyung-Tae Kang (Scientific Reports)
Abstract Inkjet printers are key technologies in manufacturing organic light-emitting diodes and quantum dot light-emitting diode panels, but precise measurement and control of inkjet droplets remains challenging. The international standard, IEC 62899-302-1, uses shadow image-based measurement with high magnification microscopes to observe picoliter-sized droplets. However, high magnification lens results in a shallow depth of field or narrow optimal measurement area, causing the blurring image if the droplet does not pass through the optimal measurement area. To solve this, we propose using the interference image-based measurement with interference fringe patterns by inkjet droplets as a tool to measure the flight speed of droplets. The interference fringe patterns can be obtained simply passing the droplet through within the light beam path, providing approximately 1000× wider measurement area compared to the shadow image-based measurement, making it practical to use in the industry. The flight speed of droplets analyzed with the interference image-based measurement at various frequencies and amplitudes of the inkjet driving voltage were compared with the shadow image-based measurement. The interference image-based measurement showed a coefficient of variation of less than 3%, showing higher repeatability than the shadow image-based measurements.